Late-Developing Supernumerary Premolars: Analysis of Different Therapeutic Approaches. (28th September 2016) - Paduano, Sergio; Rongo, Roberto; Lucchese, Alessandra; Aiello, Domenico; Michelotti, Ambrosina; Grippaudo, Cristina
Abstract : This case series describes the different potential approaches to late-developing supernumerary premolars (LDSP). LDSP are supernumerary teeth (ST) formed after the eruption of the permanent dentition; usually they develop in the premolar region of the upper and lower jaw. The choice to extract or to monitor the LDSP depends on many factors and has to be carefully planned due to the several risks that either the monitoring or the extraction could provoke. These four cases of LDSP showed different treatment plan alternatives derived from a scrupulous assessment of the clinical and radiographic information.